Regenerasi Tari Topeng Cirebon di Tengah Perubahan Budaya Generasi Muda - Rizky Oktoviyani; Naila Farah (Nazharat: Jurnal Kebudayaan, 2026)
The Cirebon Mask Dance is a traditional cultural heritage that holds historical, philosophical, and cultural identity value for the Cirebon people. However, the development of globalization, modernization, and digital culture has led to changes in the lifestyles of the younger generation, which have also influenced the regeneration process of traditional arts. This study aims to analyze the dynamics of the regeneration of the Cirebon Mask Dance amidst the cultural changes of the younger generation and to understand the various obstacles and preservation strategies undertaken by art studios and cultural actors. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through in-depth interviews, observation, and documentation of studio managers and young dancers of the Mask Dance in Cirebon. The results show that the regeneration of the Mask Dance is still ongoing, but has experienced changes in the patterns of involvement of the younger generation. Some young people still have an interest in the Mask Dance, especially through social media approaches, flexible learning, and cultural innovations that adapt to current developments. On the other hand, the regeneration process faces various obstacles such as changes in the interests of the younger generation, limited funds, minimal environmental support, and the view that traditional arts are old cultures that are less relevant to modern life.